2021
DOI: 10.1002/stc.2688
|View full text |Cite
|
Sign up to set email alerts
|

Guided wave‐based cable damage detection using wave energy transmission and reflection

Abstract: Summary Health monitoring of cables in civil engineering structures is a great challenge, because their integrity directly affects the safety of the whole structure. A magnetostrictive (MS) transducer‐based guided wave method for cable damage detection is presented in this study. A wave energy‐based method is proposed for damage localization and severity assessment. The wave energy transmission coefficient at the damage location is presented as a measure for the damage condition. Firstly, the wave dispersion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The energy-based damage index has been widely used in ultrasound-based damage detection [ 40 , 56 ]. As discussed above, local damage in the medium will lead to energy attenuation of DUW.…”
Section: Methodsmentioning
confidence: 99%
“…The energy-based damage index has been widely used in ultrasound-based damage detection [ 40 , 56 ]. As discussed above, local damage in the medium will lead to energy attenuation of DUW.…”
Section: Methodsmentioning
confidence: 99%
“…However, the parallel wire cable is a heterogeneous structure, and the AE signal generated when the cable is damaged has the characteristics of broadband, dispersion, and multimodality 32,33 . Different modes have different degrees of dispersion and different transmission speeds 34–36 . Therefore, the damage location error obtained by the existing time difference positioning is largely due to the assumption that the wave velocity is constant, which greatly affects the positioning accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Different modes have different degrees of dispersion and different transmission speeds. [34][35][36] Therefore, the damage location error obtained by the existing time difference positioning is largely due to the assumption that the wave velocity is constant, which greatly affects the positioning accuracy. Compared with the traditional positioning method, the previous research work 17 can determine the accurate broken localization of the parallel steel wire bundle (PSWB) that detects a certain steel wire with damage at a certain longitudinal position.…”
mentioning
confidence: 99%
“…Many researchers have used finite element (FE) simulations to investigate the wave propagation problems. [34][35][36][37][38][39][40][41][42] For example, Alleyne and Cawley 35 assessed the interaction of the Lamb waves and defects in plate-like structures using FE simulations. They showed that different parameters affect the sensitivity of Lamb waves to defects, including the geometry of the plate, wave mode, wave frequency-thickness, and the type of the notch defect.…”
Section: Introductionmentioning
confidence: 99%
“…The finite element method (FEM) is the most stable numerical solution technique to study the characteristics of wave propagation in different structures. Many researchers have used finite element (FE) simulations to investigate the wave propagation problems 34–42 . For example, Alleyne and Cawley 35 assessed the interaction of the Lamb waves and defects in plate‐like structures using FE simulations.…”
Section: Introductionmentioning
confidence: 99%